The Implementation of Court Decisions in Indonesia: Obstacles and Alternative Legal Solutions - Laesa Awalin; Ahmad Ahmad; Galuh Dwi Prasasti; Muhammad Yusuf; Junaidin Junaidin (Universitas Muhammadiyah Tangerang, 2023)
The implementation execution of decisions of the State Administrative Court constitutes a fundamental component in ensuring legal protection and upholding the principle of the rule of law in administrative governance. Decisions that have obtained permanent legal force (inkracht van gewijsde) are legally binding and must be complied with by State Administrative Agencies or Officials. Nevertheless, empirical realities demonstrate that a significant number of State Administrative Court decisions remain unimplemented or are implemented only partially, thereby undermining legal certainty and public trust in the judiciary. This study aims to examine the legal framework governing the execution of State Administrative Court decisions, to identify the principal obstacles affecting their implementation, and to formulate alternative legal solutions to optimize enforcement. This research employs a normative juridical method, utilizing statutory, conceptual, and case approaches. The findings reveal that ineffective execution of State Administrative Court decisions is primarily attributable to the absence of a specialized enforcement institution, inadequate coercive sanctions against non-compliant officials, and persistent structural as well as bureaucratic cultural constraints. Accordingly, the study recommends strengthening the legal enforcement mechanism, enhancing the authority of the court in supervising execution, and reinforcing accountability of State Administrative Officials in order to realize legal certainty and effective protection of citizens’ rights